Perception of dog health and attitudes towards BOAS grading among Danish owners of French bulldog - Proschowsky, Helle Friis; Springer, Svenja; Lotze, Sisse; Rafn, Frederikke; Sandahl, Zenia; Bruun, Camilla Sichlau; Fredholm, Merete; Lund, Thomas Bøker; Willesen, Jakob Lundgren; Sandøe, Peter (Frontiers in Veterinary Science, 2025)
IntroductionThe French bulldog is among the most popular dog breeds in many countries, but the breed is also commonly affected by a range of health problems. A key issue for the breed is Brachycephalic Obstructive Airway Syndrome (BOAS), and a proposed way to improve this situation in the future is selection based on a functional test known as BOAS grading. However, making effective changes in breeding requires a demand for less sick dogs and discrepancies between objective health parameters and owner-perceived health status are well-known among owners of brachycephalic dogs.MethodsIn this survey-based study, we recorded the health problems reported by French bulldog owners as well as their overall perception of health at both breed and individual dog level. We also examined how the presence of health problems influenced the owners’ plan to reacquire or recommend the breed. Finally, we investigated the French bulldog owners’ knowledge of and attitudes towards BOAS grading as a proposed means to enhance respiratory health in the breed.ResultsThe questionnaire resulted in 452 completed responses and the most commonly reported health problems were allergies (36.7%), breathing problems (29.6%), and back problems (19.0%). In total, 56% of the owners stated that French bulldogs are less healthy than other breeds, while 64% considered their own French bulldog to be healthier than other individuals of the same breed. Owners reporting that their dog had breathing problems were more likely to also report that their dog snored when awake, had heat intolerance, and was wheezing. The higher the level of experienced health problems, the less likely the owners were to reacquire the breed or recommend it to others. Two thirds of the owners had heard about BOAS grading and among the 300 respondents who wished to reacquire a French bulldog, 79% expressed that they likely (36.7%) or very likely (42.3%) would prefer a puppy from BOAS-graded parents.DiscussionIn line with previous studies, we found a high disease load among French bulldogs as well as a tendency to rate one’s own dog healthier than the average. The high level of reported BOAS symptoms indicates that owners can recognize the symptoms, yet relatively few respondents consulted a veterinarian about breathing problems – indicating some degree of normalization. However, the generally positive attitude toward BOAS grading may forecast a change of priorities among future owners of the breed.